Hubungan Beban Masalah Dengan Strategi Coping Pada Family Caregiver Pasien Hemodialisis Di Unit Hemodialisa RSUD RAA Tjokronegoro Purworejo - Kurniasih, Ratry; Lubis, Dina Putri Utami; Heryningsih, Wiwin Priyantari (Jurnal Kesehatan Samodra Ilmu (JKSI), 2025)
Background: Adherence to hemodialysis therapy in patients with chronic renal failure is a very important thing to pay attention to. If a patient undergoing hemodialysis therapy does not comply, there will be clotting of dangerous substances such as metabolic products in the blood. In undergoing treatment therapy the patient will be assisted by his family in meeting his living needs. Hemodialysis puts stress on the patient and stress on the family. The effects of these various things must be overcome with certain coping strategies for each family caregiver.Objective: To determine the relationship between burden of problems with coping strategies in family caregivers of hemodialysis patients in the hemodialysis unit at RAA Tjokronegoro Hospital. Method: non-experimental research method with descriptive quantitative category correlation, cross sectional approach. The sample was 43 families of HD patients using total sampling technique. Bivariate analysis with chi-square test.Results: The burden of problems on family caregivers of hemodialysis patients at RAA Tjokronegoro Hospital, Purworejo, shows that the majority have a burden of problems in the slightly burdened category, namely 27 people (62.8%), the coping strategies of family caregivers of hemodialysis patients show that the majority are maladaptive, 22 people. (51.2%) and There is a relationship between burden and coping strategies in family caregivers of hemodialysis patients in the hemodialysis unit at RAA Tjokronegoro Purworejo Regional Hospital with p value = p 0.008.Conclusion: There is a relationship between burden and coping strategies in family caregivers of hemodialysis patients in the hemodialysis unit at RAA Tjokronegoro Hospital.Recommendation: The results of this research are expected to identify the burden of problems experienced by family caregivers so that it can become a good support system for the healing and treatment process of HD patients.